ANALISIS KOMPARATIF PENDAPATAN USAHATANI TEBU PETANI KKP-E DAN PETANI NON KKP-E (Studi Kasus Desa Bululawang Kecamatan Bululawang Kabupaten Malang) - Ninin Khoirunnisa; Reza Prakoso Dwi Julianto (Universitas Tribhuwana Tunggadewi, 2017)
Sugarcane farming income can be increased by the good application of farming technology and the capital. This study aims to analyze sgarcane farming income between the sugarcane use Kredit Ketahanan Pangan dan Energi (KKP-E) and farmers not utilise of KKP-E. This research take loctions in Bululawang Village Bululawang Subdistrict Malang District purposefully. The determination of sample done by using simple random method. The data collection was done with the interview method, observation, and documentation. The data analysis method used farming analysis and the average different test. The research result show that between the average farming income of KKP-E farmers and non KKP-E farmers don`t have significant difference. This is due to difference componen authors costs farming between KKP-E farmers and non KKP-E farmers only about they take KKP-E or not. So, that the fundamental difference only on the where abouts interest of KKP-E.